Clinical and Epidemiological Characteristics of Hepatocellular Carcinoma in the Republic of Saha (Yakutia) - S. S. Sleptsova; S. I. Malov; E. D. Savilov; S. I. Semenov; V. K. Semenova; L. A. Stepanenko; O. B. Ogarkov; I. V. Malov (Эпидемиология и вакцинопрофилактика)
Relevance. In 2016, a resolution was adopted at the 69th World Health Assembly, the goal of which is to eliminate parenteral hepatitis in the world by 2030. In the Republic of Sakha (Yakutia), as in the Russian Federation as a whole, it is necessary to determine the starting positions for the prevalence and incidence of hepatitis B, C, and D, as the leading factors in the development of hepatocellular carcinoma. Aim: to give a clinical and epidemiological characterization of hepatocellular carcinoma in the Republic of Sakha (Yakutia) at the initial stage of the program for the elimination of viral hepatitis for subsequent analysis of its effectiveness. Materials & Methods. A clinical and epidemiological analysis of morbidity, mortality, cumulative survival in hepatocellular carcinoma in the Republic of Sakha (Yakutia) over a 10-year period (2009-2018) was carried out. Predictors for the development of hepatocellular carcinoma were analyzed based on primary medical records and a survey of 125 patients. Results and discussion. The incidence rate of hepatocellular carcinoma in the Republic of Sakha (Yakutia) over the past 10 years is 2.0 3.9 times higher than the corresponding indicator in the Russian Federation. The highest mortality from the studied pathology is noted in the Central and Polar zones of the republic. According to the materials of the cancer registry, the median cumulative survival of patients with carcinoma was 13.7 months from the date of diagnosis, which is significantly higher than ten years ago. The main risk factors have been identified, among which the leading role is played by infection with hepatitis C, B, and D. viruses. Also, alcohol abuse, diabetes mellitus, overweight, and smoking are important. Conclusion. The Republic of Sakha (Yakutia) is a hyperendemic region of the Russian Federation in terms of the incidence of hepatocellular carcinoma with a predominance of the male population in its structure. The rate of decrease in the incidence of liver cancer in the country will depend on the effectiveness of the regional program for the elimination of viral hepatitis and the decrease in the incidence of cirrhosis of the liver of non-infectious etiology.